1994
DOI: 10.1080/03670244.1994.9991416
|View full text |Cite
|
Sign up to set email alerts
|

Weaning practices and foods in high population‐density areas of Lusaka, Zambia

Abstract: A weaning practices and foods study was conducted to provide guidelines for a concurrent project on development of computer-optimized weaning blend formulations from indigenous Zambian food commodities. The study sample was selected from mothers and their children in 5 high populationdensity areas of Lusaka, the capital city of Zambia, to represent children in similar urban communities in Lusaka for whom improved weaning mixtures are to be designed. The investigation included a nutritional evaluation of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…This was due to the high intake from the food groups cereals, and roots and tubers, which contain food products with relatively low energy values, and due to the overall low fat-energy percentage of the weaning diet. Another study in Zambia investigating weaning practices in children aged 6 ± 29 months (Hayes et al, 1994), also observed low average caloric density per feeding. Secondly, the median weight of each consumed dish was 102 and 180 g for infants and toddlers respectively: this is low when compared to the maximum volume of 110 ± 200 ml for infants and 200 ± 300 ml for 1-to-3 y olds respectively, which can be eaten at one time (Cameron & Hofvander, 1983).…”
Section: Discussionmentioning
confidence: 89%
“…This was due to the high intake from the food groups cereals, and roots and tubers, which contain food products with relatively low energy values, and due to the overall low fat-energy percentage of the weaning diet. Another study in Zambia investigating weaning practices in children aged 6 ± 29 months (Hayes et al, 1994), also observed low average caloric density per feeding. Secondly, the median weight of each consumed dish was 102 and 180 g for infants and toddlers respectively: this is low when compared to the maximum volume of 110 ± 200 ml for infants and 200 ± 300 ml for 1-to-3 y olds respectively, which can be eaten at one time (Cameron & Hofvander, 1983).…”
Section: Discussionmentioning
confidence: 89%
“…However, dietary and environmental factors play major roles, with the end results being ill health and eventually death [1]. It has been reported that dietary factors such as prolonged breastfeeding (from >18 months to <24 months), low energy density of complimentary foods, factors concerning the mother (education level of the mother and low socio-economic status) and environmental factors contribute to the risk of malnutrition of children in developing countries [9,10]. The extent to which these factors affect the nutritional status of peri-urban children has not been adequately studied in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Guptill et al found that mothers' perception of the complexity of a weaning food recipe is reduced by giving them an opportunity to actually prepare the food themselves during an intervention [18]. An earlier survey of mothers indicated that kapenta was considered a good weaning food [9]. However, this response was most likely based on the contemporary nutrition education teaching that this commodity has high nutritional value.…”
Section: Pertinent Influences Which Can Modify Study Resultsmentioning
confidence: 84%
“…The present survey was preceded by an assessment for the specific community of nutritional need and commodity preferences and by determination of computer-optimized blend formulas of indigenous food components, prepared by local methods [8,9]. Testing with mothers involved not only their organoleptic perceptions, but their inclination to use individual food ingredients, judgment on practical matters such as expense and ease and time of preparation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation